Bioinspired design of an artificial peroxidase: introducing key residues of native peroxidases into F43Y myoglobin with a Tyr-heme cross-link. Issue 16 (1st April 2020) - Liao, Fei; Xu, Jia-Kun; Luo, Jie; Gao, Shu-Qin; Wang, Xiao-Juan; Lin, Ying-Wu
Abstract : An artificial peroxidase was rationally designed in F43Y Mb with a Tyr-heme cross-link by further introduction of key residues (Arg/Trp) in native peroxidase, which exhibited an activity comparable to the most efficient native HRP. Abstract : Inspired by the structural features of native peroxidases, an artificial peroxidase was rationally designed using F43Y myoglobin with a Tyr-heme cross-link by further introduction of key residues, including both a distal Arg and a Trp close to the heme group, which exhibits an enhanced peroxidase activity similar to the most efficient native horseradish peroxidase. This study provides a simple approach for design of artificial heme enzymes by the combination of catalytic elements of native enzymes with the post-translational modifications of heme proteins.